Anthropometric proile and somatotype of sailors of the spanish pre-olympic sailing team - Reyes Sánchez, L.; Morales Baños, V. (SPORT TK-EuroAmerican Journal of Sport Sciences, 2018)
The aim of this study was to describe the anthropometric characteristics and somatotype of sailors from different classes, who were part of the Spanish Preolympic Sailing Team between the years 2006 and 2014. The study included 50 Spanish sailors from the Spanish Preolympic Sailing Team. The following data were recorded: weight, height, skin folds, circumferences of arm, thigh and calf, diameters of the humerus, femur and wrist. Regarding the fat percentage, the girls had around 16-20% and 10-18 % boys. The mean somatotype of the sailors was mesomorph, apart from the Laser Radial class that leaned to endomorphic values. The conclusion is that there is an ideal anthropometric and somatotype profile in each class of ship listing, and it also depends on the position occupied by the sailor on the ship, hence the sailors who come to this ideal are more likely to succeed.